2016
DOI: 10.1016/j.ttbdis.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anaplasma phagocytophilum genotypes that are potentially virulent for human in wild ruminants and Ixodes ricinus in Central Italy

Abstract: Human granulocytic anaplasmosis (HGA) is an emerging tick-borne zoonosis worldwide. As is the case for many tick-borne diseases, the epidemiological cycle is associated to the environmental conditions, including the presence of wild vertebrate reservoir hosts, vectors, climate and vegetation. In this study a total number of 87 spleen samples of wild ruminants carcasses from Central Italy, and 77 Ixodes ricinus collected from the same dead animals were screened for Anaplasma phagocytophilum by using Real Time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…Although the role of wild boars in the epidemiology of SFGR is not completely clarified, our data suggest these animals as involved in the maintenance and spreading of D. marginatus and their related SFGR (Selmi et al, 2009;Raele et al, 2018). Although, studies from Italy (Di Domenico et al, 2016) and Spain (Ortuño et al, 2007) would suggest wild boar as candidate reservoir for R. slovaca , the detection of pathogen DNA in a single boar which not harboured any infected ticks does not allow any conclusion. In this study, the absence ofBorrelia burgdorferi s.l.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Although the role of wild boars in the epidemiology of SFGR is not completely clarified, our data suggest these animals as involved in the maintenance and spreading of D. marginatus and their related SFGR (Selmi et al, 2009;Raele et al, 2018). Although, studies from Italy (Di Domenico et al, 2016) and Spain (Ortuño et al, 2007) would suggest wild boar as candidate reservoir for R. slovaca , the detection of pathogen DNA in a single boar which not harboured any infected ticks does not allow any conclusion. In this study, the absence ofBorrelia burgdorferi s.l.…”
Section: Discussioncontrasting
confidence: 59%
“…In the Mediterranean basin, the thermophilic sheep tickDermacentor marginatus (Sulzer, 1776) parasitizes mainly ungulates, being strongly associated to wild boar populations (Nosek, 1972;Di Domenico et al, 2016;Selmi et al, 2017). In addition, adults of D. marginatus may feed on humans (Estrada-Peña and Jongejan, 1999;Otranto et al, 2014), mainly in the scalp region (Parola et al, 2009), potentially transmitting zoonotic Gram-negative bacteria such asRickettsia spp., Borrelia afzelii and Coxiella burnetii (Rehácek et al, 1991;Spitalská et al 2012;Hornok et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection rates of 100% in red deer, 95.4% in fallow deer, and 92.9% in roe deer estimated from our study are higher than values previously reported from Slovakia: red deer 17.5–53.1% [24, 57, 102]; fallow deer 66.7% [24], and roe deer 50–77% [24, 57, 102, 103]. The infection rates determined in this study are in the upper range of those confirmed by PCR in cervids from other countries of mainland Europe, where the values in red deer ranged between 1.5–86% [89, 104114], in fallow deer between 1.5–72.5% [42, 105, 106, 108, 110, 112, 115, 116] and in roe deer between 9.6–98.9% [38, 42, 89, 105–113, 117120]. The 88.9% infection rate in mouflon is higher than the values previously reported from Slovakia [57] and other European countries, where the prevalences ranged from 4% to 74.4% [42, 106, 110, 111].…”
Section: Discussionmentioning
confidence: 89%
“…For example, no A. phagocytophilum was detected in I. ricinus collected from roe deer in Slovakia and Poland [112, 118], but in other sites in Poland, 12.5% and 9% of ticks from roe deer and red deer, respectively, were found to be infected [58]. For engorged ticks from cervids in Italy, a 31.2% prevalence [113] or 29.9% positive pools [128] were found, but no information on the tick developmental stage was given. In another study from Italy, a prevalence of 11% and 5.4% was detected for nymphs/adults and larvae, respectively [129].…”
Section: Discussionmentioning
confidence: 99%